Functional characterization of platelets in patients with arterial erectile dysfunction. (29th July 2014) - La Vignera, S.; Condorelli, R. A.; Burgio, G.; Vicari, E.; Favilla, V.; Russo, G. I.; Cimino, S.; Morgia, G.; Calogero, A. E.
Summary Arterial erectile dysfunction (ED) is commonly associated with classic cardiovascular and metabolic risk factors, such as smoking, hypertension, diabetes mellitus, dyslipidaemia and obesity. However, some patients with arterial ED do not present any cardiovascular risk factor. As mean platelet volume (MPV) has been shown to be directly related to the cardiovascular risk and the percentage of platelets expressing the vitronectin receptor (αVβ3), involved in the early stages of platelet adhesion, is higher in patients with ED, the present study was undertaken to evaluate MPV and αVβ3 in 15 patients with arterial ED not associated with any cardiovascular risk factor. Their MPV and αVβ3 values were compared with those of men with normal penile haemodynamic. Patients with arterial ED had a mean value of MPV (11.25 vs. 9.88 fL; p < 0.001) and a percentage of platelets expressing the αVβ3 (7.39 vs. 2.07%; p < 0.001) significantly higher compared to controls. A negative correlation was observed between peak systolic velocity and MPV (r = 0.916; p < 0.001) or αVβ3 (r = 0.930; p < 0.001), whereas MPV and αVβ3 correlated positively (r = 0.908; p < 0.001). In conclusion, this study showed for the first time that MPV and the percentage of platelet expressing αVβ3 are significantly higher in patients with arterial ED compared to controls. We speculate that these parameters of platelet function may be envisaged as markers of cardiovascular risk in patients with arterial ED.